Usługi edukacyjne w przestrzeni europejskiej - kryteria i wskaźniki oceny - Pluta-Olearnik, Mirosława; Olearnik, Janusz (Education Services in Europe Criteria and Assessment Indicators, 2006)
This paper presents a full title of the 29 indicators for monitoring performance and progress of education and training systems in Europe. The issue of indicators and benchmarks is central to the monitoring and progress of the HE systems too. Member states may set themselves "reference criteria" (benchmarks) for 2004 but the final list of proposed indicators and benchmarks will be proposed up by the Commission. The implementation of the work programme requires continuous support from a standing group on indicators and benchmarks and the open method of coordination.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 285-293